The The Free Nutritious Meal Policy in Primary Education Institutions in South Sulawesi (Evaluation of the First Semester of MBG Implementation): The Free Nutritious Meal Policy in Primary Education Institutions in South Sulawesi - Kahar, Abdul; Giri Prawiyogi, Anggy (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to evaluate the implementation of the Free Nutritious Meal (Makan Bergizi Gratis/MBG) policy in elementary schools across South Sulawesi Province during its first semester of execution. The research background stems from the urgency of improving school-age children’s nutrition as part of a broader human resource development strategy. This study employs a descriptive qualitative approach using an evaluation study design. Data were collected through in-depth interviews with principals, teachers, and parents; direct observation of meal distribution processes; and analysis of policy documents and implementation reports. The evaluation approach adopted in this study is the Discrepancy Evaluation Model (DEM) developed by Malcolm Provus. This model focuses on analyzing the gap between the established standards of the MBG policy and its actual implementation in schools. The evaluation process includes: (1) identifying program standards or criteria, such as meal portions, nutritional content, and distribution mechanisms; (2) measuring actual performance through observations and interviews; (3) comparing standards and implementation outcomes to detect discrepancies; and (4) analyzing the causes of these discrepancies and providing recommendations for improvement. This approach allows the researcher to systematically identify areas of strength as well as areas needing improvement, providing a strong basis for data-driven decision-making. Data analysis employed Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the MBG program has had a positive impact on student attendance, learning motivation, and nutritional awareness among pupils. However, challenges were identified, including budget constraints, unequal distribution of food supplies, and a lack of training for school nutrition staff. This study provides practical contributions for local governments and education offices to improve program effectiveness, as well as academic contributions for developing school-based nutrition policy studies. Recommendations include strengthening cross-sectoral coordination, optimizing budget allocation, and enhancing the capacity of school personnel. Thus, this initial evaluation serves as an important foundation for formulating sustainable policies to support children’s optimal growth and development.